RANCANG BANGUN SISTEM INFORMASI PENYEWAAN ALAT OUTDOOR DENGAN MENERAPKAN ALGORITMA FIRST IN FIRST OUT - Maspaeni; Nurwijayanti, Karina; Yani, Ahmad; Rosidi, Haikal (Universitas Serang Raya, 2023)
The rental system currently implemented at Mandala Outdoor Equipement requires customers who want to rent outdoor equipment to come directly or via telephone/WA communication to Mandala Outdoor Equipement. Rental of outdoor equipment sometimes causes problems, such as customers who are disappointed because they were previously confirmed to be able to rent outdoor equipment, after receiving information that they could not or that it was canceled by the provider because it turned out the stock had run out, even though this happens. After all, sometimes they prioritize renters with proximity factors because of the courage of new renters. with higher rental costs. Based on these existing problems, this research aims to build a website-based information system by applying the First in First Out (FIFO) algorithm for outdoor equipment rental at Mandala Outdoor Equipment. The method used in this research is the waterfall method. The result of this research is an outdoor equipment rental application by applying the FIFO algorithm to the web-based Mandala Outdoor Equipment so that rentals can be done via the website (anywhere and at any time) and rentals are served according to the rental time sequence (First in First Out). From the results of testing the application using a separate black box, seen from the functional aspect, both features and access rights, everything went well, successfully, and validly.